Preferences and emotional response to weight‐related terminology used by healthcare professionals to describe body weight in people living with overweight and obesity. Issue 5 (9th June 2021) - Brown, Adrian; Flint, Stuart W.
Summary: Previous studies have explored people's perceptions of weight‐related terminology; however, to date, limited data has explored the emotional response to weight‐related terms used by healthcare professionals (HCPs). This study explored the preferences and emotional responses of terms used by HCPs to describe body weight and of parents to describe their children's weight. A total of 2911 adults completed an online cross‐sectional survey, with 1693 living with overweight or obesity (mean age 49.2 years [SD 12.5], female (96%), median body mass index (BMI) 31.4 kg/m 2 [28.1, 36.5]). The survey explored preferences of 22 weight‐related terms using a 5‐point Likert scale and their emotional response to these terms (using 7‐core emotions). Parents also indicated preferences and emotional responses to terms used to describe their children's weight. Respondents completed the modified weight bias internalization scale to examine how this may impacted preferences. 'Weight', "unhealthy weight" and "overweight" were the three preferred terms, while "super obese", "chubby", and "extra‐large" were least preferred in people living with overweight and obesity. Parents preferred 'weight', "unhealthy weight" and "body mass index", and least preferred "fat", "extra‐large" and "extremely obese" when describing their children's weight. All terms elicited a negative emotional response. The most commonly emotion was sadness for terms to describe adult's bodyweight, and anger for terms used to describe children's weight. All BMI categories reported disgust with terms incorporating "obese". Our results offer novel insight into the preferred terminology and emotional responses to terminology used by HCPs for both adults and parents to describe their children's weight.